2016 IEEE International Conference on Communications (ICC) 2016
DOI: 10.1109/icc.2016.7511429
|View full text |Cite
|
Sign up to set email alerts
|

Link adaptation design for ultra-reliable communications

Abstract: Abstract-The fifth generation (5G) of cellular networks is expected to provide connectivity for a wide range of services. This requires the network to encounter novel features. Ultrareliable communications (URC) is one of the considered features, which provides a certain level of communication service almost all the time. This is essential in order to support mission-critical applications, such as industrial automation, public safety, and vehicular communications. This paper studies link adaptation optimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 12 publications
0
49
0
Order By: Relevance
“…As a result, the optimal objective value of problem (22) in the lth iteration is no larger than that achieved by the solution w (I,l−1) n 's and t (I,l−1) n 's, i.e., Monotonic convergence of Algorithm 1 is thus proved. Next, since in Algorithm 1 we use lower-bound to approximate the non-concave functions in problem (15), as shown in (18), (19), and (21), any feasible solution to problem (22) satisfies all the constraints of problem (15).…”
Section: A Proof Of Propositionmentioning
confidence: 87%
See 1 more Smart Citation
“…As a result, the optimal objective value of problem (22) in the lth iteration is no larger than that achieved by the solution w (I,l−1) n 's and t (I,l−1) n 's, i.e., Monotonic convergence of Algorithm 1 is thus proved. Next, since in Algorithm 1 we use lower-bound to approximate the non-concave functions in problem (15), as shown in (18), (19), and (21), any feasible solution to problem (22) satisfies all the constraints of problem (15).…”
Section: A Proof Of Propositionmentioning
confidence: 87%
“…First, it can be shown that in the lth iteration of Algorithm 1, the solution obtained in the (l − 1)th iteration is also feasible to problem (22) givenŵ (I) n = w (I,l−1) n (thuŝ a n = a (l−1) n andb n = b (l−1) n ) andt is achievable to problem (22) in the lth iteration. As a result, the optimal objective value of problem (22) in the lth iteration is no larger than that achieved by the solution w (I,l−1) n 's and t (I,l−1) n 's, i.e., Monotonic convergence of Algorithm 1 is thus proved. Next, since in Algorithm 1 we use lower-bound to approximate the non-concave functions in problem (15), as shown in (18), (19), and (21), any feasible solution to problem (22) satisfies all the constraints of problem (15).…”
Section: A Proof Of Propositionmentioning
confidence: 99%
“…However, in the presence of random link blockage and high path-losses, mmWave feedback links are equally unreliable and thus results in redundant retransmission. On the other hand, allowable latency determines a strict upper limit on the number of retransmission attempts [17].…”
Section: A Prior Workmentioning
confidence: 99%
“…8·0.143 ms > 1 ms). Since relying on a single (very conservative) transmission would have a significant cost on the spectral efficiency [9], we study the case where the HARQ RTT is reduced to 4 TTIs in order to allow room for one HARQ retransmission. A diagram of the HARQ procedure with reduced RTT is presented in Fig.…”
Section: B Short Harq Rttmentioning
confidence: 99%
“…Related to the former, the study in [8] evaluates the downlink latency performance under different TTI durations and load conditions, assuming a mixture of high-priority bursty traffic and best-effort mobile broadband (MBB) traffic. In [9], a link adaptation strategy is presented where the modulation and coding scheme (MCS) is selected according to the target reliability and feedback channel imperfections, assuming that one hybrid automatic repeat request (HARQ) retransmission is allowed.…”
Section: Introductionmentioning
confidence: 99%